196k views
0 votes
Given x=-3, y=6, and z=-4 xz/-2y

Given x=-3, y=6, and z=-4 xz/-2y-example-1

2 Answers

3 votes

Answer: -1

Explanation:

xz/-2y, given x=-3, y=6, and z=-4

------------

xz/-2y

=(-3)(-4)/-2(6) ⇔ substitute x y and z value

=12/-12 ⇔ calculate it

=-1 ⇔ simplify fraction

Hope this helps!! :)

Please let me know if you have any question

User Silverfighter
by
5.9k points
7 votes

Answer:

-1

Explanation:

sub in the values of x, y and z into the equation

you get:

(-3)(-4)/(-2)(6)

= 12/-12

= -1

User MadAsAHatter
by
5.0k points